2022
DOI: 10.2147/ndt.s365758
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Early Neurological Deterioration and Functional Outcome in Acute Ischemic Stroke: The Importance of Large Artery Disease, Hyperglycemia and Inflammatory Blood Biomarkers

Abstract: Background Early neurological deterioration (END) in acute ischemic stroke (AIS) can be associated with poor outcome. The aim of this study was to investigate the association between infarction subtypes, biomarkers and END, and to identify patients with risk of unfavorable functional outcome. Materials and Methods This prospective study enrolled 101 patients with AIS. Neurological status was evaluated according to NIHSS at acute onset, on days 2, 3, and 90. END was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 44 publications
(91 reference statements)
0
21
0
Order By: Relevance
“…Inflammatory factors can not only induce cell death responsible for functional injury ( 5 ), but also underlie the development of atherosclerosis by regulating macrophages, cytokines, and leukocyte adhesion molecules to induce endothelial dysfunction, plaque formation and rupture, platelet aggregation, and thrombosis ( 6 , 7 ). Therefore, some inflammatory cytokines are investigated as predictors of functional outcomes after stroke ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory factors can not only induce cell death responsible for functional injury ( 5 ), but also underlie the development of atherosclerosis by regulating macrophages, cytokines, and leukocyte adhesion molecules to induce endothelial dysfunction, plaque formation and rupture, platelet aggregation, and thrombosis ( 6 , 7 ). Therefore, some inflammatory cytokines are investigated as predictors of functional outcomes after stroke ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate analysis for the influence of facility features on head elevation revealed an interesting result, in that facilities with board-certified rehabilitation doctors were more cautious regarding head elevation in BAD, AT, and CE, as situations in which neurological deterioration often occur [24][25][26]. Rehabilitation doctors may prioritize the maintenance of cerebral blood flow when considering head positioning.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that patients with LAA have a greater risk of developing END after thrombolysis in AIS. 5,22,23 Another study found that acute neurological deterioration was observed at a median of 3.6 h from arrival in nearly 20% patients with large-vessel occlusion and mild stroke. 24 In our study, there was a significant association between the occurrence of VEND and underlying LAA, especially ICAD.…”
Section: Discussionmentioning
confidence: 99%